Nivel De Conocimiento De Prevención Y Factores De Riesgo Del Cáncer De Mama En Mef (20-45 Años). Sector San José, Cantón Babahoyo. Abril – Octubre 2014 - Arteaga Maliza, Adrian Geovanny (2013)
Breast cancer is a disease; where a single cell product of a series of somatic mutations or germline. In the world almost 22 million cases of cancer will be diagnosed in 2030, compared to 14 million in 2012 due to the increase of this disease in developing countries, says a study published by the World Health Organization(WHO). The prevalence and mortality of breast cancer will increase in the coming years, since according to WHO estimates, by 2025 there will be up to 2.5 million new cases and up to 800,000 deaths.